Problem Based Learning Dalam Pembelajaran Kewarganegaraan Sebagai Upaya Meningkatkan Prestasi Belajar Siswa Kelas XI IPS 2 SMA Negeri 1 Malaka Barat Tahun Pelajaran 2022/2023 - Marselina Fahik (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this study was to evaluate the effectiveness of the Problem Based Learning (PBL) model in improving student learning outcomes in SMA. The research was conducted in two cycles at SMA Negeri 1 West Malacca. Data were obtained through observing learning activities, formative tests, and summarizing student scores. The results showed that there was a significant increase in cycle II compared to cycle I. The number of students who completed learning increased from 23 to 32 students, the average score of formative tests increased from 69.57 to 84.29, and the percentage of learning completeness increased. from 65.71 to 91.43. PBL implementation yields gains in increasing student participation, student-teacher interaction, student engagement, and overall student learning outcomes. Problem-based learning encourages students to engage in critical thinking, collaboration and discussion. The integration of relevant information sources also increases students' understanding of the subject matter. In conclusion, the application of Problem-Based Learning (PBL) significantly improves student learning outcomes and makes a positive contribution in the context of learning in SMA.